Percentage and Length of The Broiler Digestive Tract that Got Rations Contains Fermented Dragon Fruit Skin - C. L., Manaek; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
This study aims to determine the effect of ration containing fermented dragon fruit rind on the percentage and length of the digestive tract of broilers. Held for 5 weeks. The treatment is given since the chicken is 1 week old. The broiler used is type MB 202, produced by PT Japfa Comfeed Tbk as many as 90 tails with a homogeneous body weight. Using a completely randomized design (CRD) with 3 treatments and 6 replications, each repetition consisted of 5 broiler chickens aged 1 week. The treatments that were tried in this study were R0: ration without fermented dragon fruit rind, R1: ration with dragon fruit rind fermented by 5% in ration, R2: ration with fermented dragon fruit rind as much as 7% in ration. The observed variables included gizzard percentage, proventriculus percentage, percentage and length of small intestine (duodenum, jejenum, ileum), percentage and length of cecum. The results showed that the provision of rations containing fermented dragon fruit peel at 7% level affected the length of the duodenum and the length of the ileum. But at the level of 5% -7% does not affect the percentage of gizzard, percentage of proventriculus, percentage of duodenum, percentage of jejenum, percentage of ileum, percentage of caecum, length of jejenum, and length of caecum. The conclusion of this study is the administration of fermented dragon skin peel at 7% level resulting in duodenal length and ileum length lower than control (R 0 ). Keywords: Broiler, fermentation, dragon fruit skin